Total Physical Response In English Camp For New Students Of Lombok Business Academy - Muhlisin, Muhammad; Imran, Fathurrahman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
One of the innovative approaches to enhance students' confidence in communicating using English is through English Camp activities. This research is an effort the director of the Lombok Business Academy (AKBIL) and Lecturers of the Faculty of Culture, Management, and Business (FBMB), especially Lecturers in the English Education Study Program. This research is also a form of follow-up to the collaboration carried out by AKBIL and FBMB. AKBIL New Students need to be given motivation and confidence in speaking English through English Camp activities. English Camp is intended as a fun learning activity that is carried out indoors/outdoors which lasts for 3 days. Through these activities, students have gained an understanding of basic theories in communicating using English. The method used in this study is a qualitative method, a data collection technique carried out by the author through literature studies, observations, interviews, and questionnaires. Literature studies are used to help authors find relevant information related to English Camp. Observation is used to directly observe the participants' activities and dynamics during the English camp. Interviews were conducted by the author to participants to find out the success of event planning. The analysis of this interview data includes three activity flows, namely data reduction, data presentation, and conclusion drawn. The questionnaire was used to determine the success of the English Camp 2024 event planning, in collecting data through the dissemination of the author's questionnaire using the Likert Scale.